Contribuições da análise do comportamento para a compreensão da leitura e escrita investigações empíricas e diálogos com outras áreas de conhecimento - Volume 2 - Melo, Raquel Maria de (Editora Oficina Universitária, 2021)
This book is part of a two-volume collection on reading and writing. In this volume II, 24 researchers, linked to 10 Brazilian universities, make a synthesis of empirical investigations on teaching and learning of reading and writing, with different populations (e.g., adults, children with Intellectual and Hearing Disabilities), from the perspective of the Analysis of the Behavior, science with a strong tradition in Brazil. Dialogues between this science and other areas of knowledge (speech therapy, linguistics and education) are also presented. According to the National Literacy Policy (PNA) the literacy process must be based on scientific evidence, which must guide the curricular structure and teaching practices. This work is aimed at undergraduate and graduate students and professionals in psychology and related areas. These will find here subsidies for carrying out new investigations and for making decisions based on evidence, in reading and writing teaching contexts.